Pengembangan Media Pembelajaran berbasis Google Sites berbantuan Aplikasi Quizizz pada Materi Lingkungan dan Kependudukan Kelas XI SMAN 5 Gorontalo Utara - Haluti, Istian; Eraku, Sunarty S.; Mohamad, Nurdin (Universitas Pendidikan Ganesha, 2025)
This study aims to develop Google Site-based learning media assisted by the Quizizz application on the Environment and Population learning material. This study is a research and development (R&D) study. This method was then used to create a specific product and to test the effectiveness of the product. The development model used in this study was the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The findings indicate that the assessment of media experts is 85.33%, material experts are 86.66%, question experts are 90%, and Geography teachers' is 84.28%. These values are categorized as very valid according to the validation criteria used. Furthermore, students' assessment of the product is 90.11% and is also categorized as very valid. It can be concluded that the development of Google Site-based learning media assisted by the Quizizz application on the Environment and Population learning material produces a suitable learning media product for use in the geography learning process, especially in the learning material of Environment and Population.